USING LLM AND GENERATIVE MODELS IN THE DEVELOPMENT OF VOICE AND WEB ASSISTANTS (American Journal of Technology and Applied Sciences, 2023)
This article examines the application of generative AI models, including large-scale language models (LLM) and diffusion models, in software development. The article analyzes their use, advantages, limitations, and impact on software development lifecycle. Particular attention is paid to automatic code generation, testing, and visual interface design.